ACE2, Much More Than Just a Receptor for SARS-COV-2 - Samavati, Lobelia; Uhal, Bruce D. (Frontiers in Cellular and Infection Microbiology, 2020)
The rapidly evolving pandemic of severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection worldwide cost many lives. The angiotensin converting enzyme-2 (ACE-2) has been identified as the receptor for the SARS-CoV-2 viral entry. As such, it is now receiving renewed attention as a potential target for anti-viral therapeutics. We review the physiological functions of ACE2 in the cardiovascular system and the lungs, and how the activation of ACE2/MAS/G protein coupled receptor contributes in reducing acute injury and inhibiting fibrogenesis of the lungs and protecting the cardiovascular system. In this perspective, we predominantly focus on the impact of SARS-CoV-2 infection on ACE2 and dysregulation of the protective effect of ACE2/MAS/G protein pathway vs. the deleterious effect of Renin/Angiotensin/Aldosterone. We discuss the potential effect of invasion of SARS-CoV-2 on the function of ACE2 and the loss of the protective effect of the ACE2/MAS pathway in alveolar epithelial cells and how this may amplify systemic deleterious effect of renin-angiotensin aldosterone system (RAS) in the host. Furthermore, we speculate the potential of exploiting the modulation of ACE2/MAS pathway as a natural protection of lung injury by modulation of ACE2/MAS axis or by developing targeted drugs to inhibit proteases required for viral entry.